ANALISIS NILAI-NILAI EDUKATIF DALAM NOVEL “LOVE IN PESANTREN” SEBAGAI REFORMULASI POLA INTERAKSI GURU DAN MURID DI PESANTREN - Achmat Mubarok; Asrul Anan (Universitas Yudharta Pasuruan, 2019)
Teacher and student interaction is very important in supporting educational success. A good pattern of interaction between teacher and student will create an educational and enjoyable atmosphere. One of the novels by Shachree M. Daroini entitled